PENERAPAN ALGORITMA COLABORATIVE FILTERING UNTUK PEMBERIAN REKOMENDASI PADA PRODUK KAIN TENUN (Studi Kasus Kain Tenun Parengan) - Miftahus Sholihin (Universitas Islam Lamongan, 2017)
Electronic commerce (e-commerce) is a concept that can be described as a process of buying and selling goods on the internet or the process of buying and selling or exchange of products, services, and information through information networks including the Internet. In developing e-commerce should be able to provide recommendations to customers. This recommendation aims to provide an overview of information about products that are considered in accordance with the wishes of customers. The method used in this research is Item Based Collaborative Filtering, where the system will look for similarity purchase model (similarity item) With others. The system will search for ratings between items by level The similarities exist. Once the item-to-item rating is obtained, this rating will be used to calculate the value Similarity between items using the Adjusted Cosine Similarity approach. The last process is to calculate the rating prediction value that customers have never done to a particular item. This approach uses Weigted Sum formula results from predicted value will be made recommendations to customers